Collaboration tools for project managers : how to choose, get started, and collaborate with technology - Harrin, Elizabeth (Project Management Institute, Inc., 2016)
Showing project managers how to lay a solid foundation for virtual collaboration, this book provides the latest information, success stories, and an easy-to-follow guide to implementing online collaboration tools and helping to overcome obstacles. --